2020
DOI: 10.1038/s41598-020-62455-4
|View full text |Cite
|
Sign up to set email alerts
|

Survival factor SvfA plays multiple roles in differentiation and is essential for completion of sexual development in Aspergillus nidulans

Abstract: The first member of the velvet family of proteins, VeA, regulates sexual development and secondary metabolism in the filamentous fungus Aspergillus nidulans. in our study, through comparative proteome analysis using wild type and veA-deletion strains, new putative regulators of sexual development were identified and functionally analyzed. Among these, SvfA, containing a yeast survival factor 1 domain, plays multiple roles in the growth and differentiation of A. nidulans. Deletion of the svfA gene resulted in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…For mycelial production, strains were cultivated in liquid complete medium (YCGMM), which was the GMM supplemented with 0.15% yeast extract and 0.15% casamino acid. To observe conidiophores, conidia were inoculated on solid YCGMM agar blocks and coverslip-cultured for 24 hrs ( Lim et al., 2020a ). To induce sexual development, the vegetative mass mating (VeM) method was used ( Lim and Park, 2019a ).…”
Section: Methodsmentioning
confidence: 99%
“…For mycelial production, strains were cultivated in liquid complete medium (YCGMM), which was the GMM supplemented with 0.15% yeast extract and 0.15% casamino acid. To observe conidiophores, conidia were inoculated on solid YCGMM agar blocks and coverslip-cultured for 24 hrs ( Lim et al., 2020a ). To induce sexual development, the vegetative mass mating (VeM) method was used ( Lim and Park, 2019a ).…”
Section: Methodsmentioning
confidence: 99%
“…A. nidulans wild-type (WT), svfA -deletion (Δ svfA ), and complementary (C’ svfA ) strains were obtained from our previous studies and maintained in Aspergillus glucose minimal medium (GMM) [ 26 , 34 ]. The C’ svfA strain was generated by the re-introduction of the svfA gene to the Δ svfA strain [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, we identified SvfA as a global transcription factor VeA-dependent protein that has only one domain: a yeast survival factor1 (Svf1) homologous protein. SvfA plays a role in the growth and development of A. nidulans ; it regulates vegetative growth, functions in oxidative and cold stress responses, and affects conidial germination, conidial production, and completion of sexual development [ 26 ]. A. nidulans can produce two forms of the SvfA protein; only the production of the larger form is sexual-development-specific [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations